The pre-weaning growth of lambs from crossbreeding between Garut ewes with Dorper rams - Ichda Rufaida Athifa; Aprilianna Putri Zahra Nafsina Luvita Sari; Dyah Maharani; I Gede Suparta Budisatria; Sigit Bintara; Yudi Guntara Noor; Rahmat Hidayat; Panjono Panjono (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Athifa IR, Sari APZNL, Maharani D, Budisatria IGS, Bintara S, Noor YG, Hidayat R, Panjono. 2022. The pre-weaning growth of lambs from crossbreeding between Garut ewes with Dorper rams. Biodiversitas 23: 5738-5743. This study was aimed at determining the productivity of lamb from mating between Garut ewes and Dorper rams. The animals used were 108 sheep. A total of 98 heads of Garut ewes were randomly divided into two groups; the first group was mated with Dorper rams (5 heads), while the second group was mated with Garut rams (5 heads) as a control group. The data observed were birth weight, weaning weight, average daily gain (ADG), reproduction index (RI), and productivity index (PI). The data were analyzed with an independent sample T-Test. Birth weight, weaning weight, and ADG of Garut and Dorper crossbred lambs were 2.20±0.54 and 2.60±0.71 kg; 14.91±3.57 and 16.27±3.69 kg; and 90.21±32.11 and 119.12±42.64 g/day, respectively. Pre-weaning growth of Dorper-crossed lambs was higher (P<0.05) than those of Garut lambs. The RI and PI of Garut ewes mated with Garut and Dorper rams were 3.15±1.38 and 2.87±1.33 head/year; and 32, 10±15.53 and 38.91±21.00 kg/year, respectively. The PI of ewes mated with Dorper rams was higher (P<0.05) than that of Garut ewes mated with Garut rams. It is concluded that the cross of the Garut ewes with the Dorper rams improved productivity by increasing the pre-weaning growth of the lambs.